Single Interdigital Transducer as Surface Acoustic Wave Impedance Sensor. (2017) - Nguyen, V.H.; Richert, S.; Park, H.; Böker, A.; Schnakenberg, U.
Abstract: Surface acoustic wave (SAW) devices are well-known for gravimetric sensor applications. In biosensing applications, chemical- and biochemically evoked adsorption processes at surfaces are detected in liquid environments using delay-line or resonator sensor configurations, preferably in combination with appropriate microfluidic devices. In this paper, a novel SAW-based impedance sensor type is introduced which uses only one interdigital electrode transducer (IDT) simultaneously as SAW generator and sensor element. It is shown that the amplitude of the reflected S11 signal directly depends on the input impedance of the SAW device. The input impedance is strongly influenced by mass adsorption which causes a characteristic and measurable impedance mismatch.